Analysis and Treatment of Ash Deposition in SCR Denitration Equipments of W Boiler - Fangyong WANG; Wenjie LI (Zhongguo dianli)
The W type flame boiler in a power plant is burned with high ash anthracite. The serious ash accumulation on the SCR denitrification reactor catalyst, the diversion plate, the rectifying grille and the supporting steel beam can lead to the uneven flow of the flow field and the blockage of the catalyst, which affects the performance of the SCR denitrification system. According to the operation experience and the CFD technology, the reasons for the ash accumulation in the SCR denitrification devices are improper design, unreasonable catalyst type selection, uneven flow field, poor soot blowing, long term low load operation and coal ash far beyond the design value. Based on the optimization of the flue gas flow field and the 1︰10 physical model test, the diversion plate, the rectifying grid and the top flue were reformed; the honeycomb type catalyst was replaced by the plate type catalyst; and the sonic soot blower was added. Three months after the transformation, the internal inspection of the denitrification devices was carried out. The horizontal flue of the reactor and the ash accumulation of the diversion plate were reduced obviously. No ash accumulation was found in the rectifying layer. No accumulated ash and blockage were found on the surface of the catalyst and the. It is proved that the measures taken have solved the problem of the internal dust accumulation and the catalyst plugging in the SCR reactor effectively.